Redescription of Mactra bonariensis Philippi, 1893 and designation of a neotype - Pérez, Leandro Martín (2011)
During an ongoing revision of the Paraná Formation fauna of Argentina, the taxonomic status of Mactra bonariensis Philippi, 1893, was reassessed. The morphological characters of M. bonariensis provided in the original description and illustration do not allow clear delimitation of the species. The absence of type material of this species, coupled with difficulties in resampling the type locality due to urbanization, necessitates designation of a neotype. No records of this taxon were found in palaeontological and malacological collections. However, material collected from the Paraná Formation at 'La Juanita' (Entre Ríos, Argentina) comes from beds equivalent to those exposed at the locality from which Philippi described the original material. As this species may be confused with Quaternary and extant species from the region, a redescription is provided and a neotype designated.